Thermal reference points as an index for monitoring body temperature in marine mammals - Melero Asensio, Mar; Rodríguez Prieto, Víctor; Rubio García, Ana; García Párraga, Daniel; Sánchez-Vizcaíno Rodríguez, José Manuel (BMC Research Notes, 2015)
BACKGROUND Monitoring body temperature is essential in veterinary care as minor variations may indicate dysfunction. Rectal temperature is widely used as a proxy for body temperature, but measuring it requires special equipment, training or restraining, and it potentially stresses animals. Infrared thermography is an alternative that reduces handling stress, is safer for technicians and works well for untrained animals. This study analysed thermal reference points in five marine mammal species: bottlenose dolphin (Tursiops truncatus); beluga whale (Delphinapterus leucas); Patagonian sea lion (Otaria flavescens); harbour seal (Phoca vitulina); and Pacific walrus (Odobenus rosmarus divergens). RESULTS The thermogram analysis revealed that the internal blowhole mucosa temperature is the most reliable indicator of body temperature in cetaceans. The temperatures taken during voluntary breathing with a camera held perpendicularly were practically identical to the rectal temperature in bottlenose dolphins and were only 1 °C lower than the rectal temperature in beluga whales. In pinnipeds, eye temperature appears the best parameter for temperature control. In these animals, the average times required for temperatures to stabilise after hauling out, and the average steady-state temperature values, differed according to species: Patagonian sea lions, 10 min, 31.13 °C; harbour seals, 10 min, 32.27 °C; Pacific walruses, 5 min, 29.93 °C. CONCLUSIONS The best thermographic and most stable reference points for monitoring body temperature in marine mammals are open blowhole in cetaceans and eyes in pinnipeds. Centro de Vigilancia Sanitaria Veterinaria (VISAVET) TRUE pub